Komunikasi Efektif Berbasis Kearifan Lokal dalam Pengelolaan Mina Padi di Komunitas Tani: Studi Kasus Kelompok Tani Cimindi Kabupaten Cilacap - Anita Agustina Wulandari; Suprihatin Suprihatin; Aulia Afniar Rahmawati; Mochammad Arkansyah (Universitas Merdeka Malang, 2026)
This study examines group communication patterns in local wisdom-based mina padi management within the CIMINDI farmer group in Cilacap, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation, and analyzed through coding, categorization, and thematic interpretation. The findings reveal that communication does not follow a single structure but forms a hybrid communication pattern, combining centralized leadership with participatory interaction in a dynamic and contextual manner. This pattern is shaped by local wisdom values, including mutual cooperation, deliberation, the use of local language, and social trust, which strengthen group cohesion. The communication pattern contributes to successful mina padi management, reflected in increased productivity, cost efficiency, strong social relations, and minimal internal conflict. This study highlights that local wisdom functions not only as cultural values but also as a communicative structure that enables adaptive and sustainable group interaction.